1996
DOI: 10.1207/s15327752jpa6603_5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Culture-Free Self-Esteem Scale Means From Different Child and Adolescent Groups

Abstract: The Culture-Free Self-Esteem Inventory (CFSEI-2) was administered to 7 groups of children: 84 White Catholic school students from a New Orleans suburb, 78 White rural public school students from Virginia, 62 Hispanic Migrant student from Florida, 90 Aboriginal and White students from an isolated Canadian community, 199 African American students attending an inner city school, 60 Hispanic and White international students from Venezuela, and 61 Innuit students from isolated community in Labrador. The four elder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Finally, this study continues a line of research attempting to validate self-report measures for use within an African American population (Hare 1996;Holaday et al 1996;Politano et al 1986;Steele et al 2006). The goal of similar studies is not to criticize the measure developers, but to suggest that further validation is needed across various ethnic and cultural groups to fully understand the merits of different measures.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, this study continues a line of research attempting to validate self-report measures for use within an African American population (Hare 1996;Holaday et al 1996;Politano et al 1986;Steele et al 2006). The goal of similar studies is not to criticize the measure developers, but to suggest that further validation is needed across various ethnic and cultural groups to fully understand the merits of different measures.…”
Section: Discussionmentioning
confidence: 85%
“…While some of the measures have been in use for decades, their suitability for assessing individuals from diverse backgrounds remains unclear (Hare 1996;Holaday et al 1996;Twenge and Crocker 2002). As Ben-Porath (1990) noted, steps are needed to determine whether the meaning and interpretations of an instrument developed in one culture can be applied for use in another.…”
Section: Introductionmentioning
confidence: 99%
“…Holaday, M., Callahan, K., Fabre, L., & Hall, C. (1996). A comparison of culture-free self-esteem scale means from different child and adolescent groups.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the allegedly "culture free" CFSEI-2 is another example of the ways in which AFL struggles with cultural relevancy. Holaday, Callahan, Fabre, and Hall (1996) administered the CFSEI-2 to 634 children from seven different cultural backgrounds, including Inuit, and concluded that the CFSEI-2 is actually not "culture-free." Specifically, Holaday et al (1996) found that:…”
Section: Youth Leadership Development Through Sport Recreation and mentioning
confidence: 99%
“…For example, a recent Rorschach study reporting local norms for individuals living in Fresno, California, revealed significant differences between Exner's (1993) adult normative data and the Fresno data (Shaffer, Erdberg, & Haroian, 1998). In another study a "culture-free" test developed for White Canadian children had norms that were not appropriate for seven culturally diverse groups of children living in Venezuela, Lolrisiana, Virginia, Labrador, Florida, and within the Arctic Circle (Holaday et al, 1996). Furthermore, without supporting research, tests and techniques normed on young individuals should not be assumed to have validity for clients 30 to 60 years older.…”
Section: Specific Variables and Discussionmentioning
confidence: 99%